Influence of Germination Time on Some Physical Properties of Germinated Paddy (Oryza sativa L.) - Kamara, Joseph Sherman; Allie , Georgiana (Journal of Postharvest Technology, 2014)
The physical properties of grains are important factors in designing efficient food processing, handling and storage systems. In this work we investigated the influence of degree of germination (in terms of the duration of germination treatment) on some geometric, mass-related and flow-related properties of germinated paddy grains. Paddy grains germinated at 38oC and 85% relative humidity over a period of 24, 48 or 72 hours and dried to a moisture content of about 11% (wet basis) after or without parboiling, were used for physical characterization. Results show that degree of germination had a significant influence on the mass properties of paddy grains, with evidence of linear decrease in both bulk density and 1000-grain mass with increasing germination time. A similar trend was observed for the porosity of both raw and parboiled germinated paddy grains.